Implementation of Inverse Kinematics System in Robotic Arm for Glass Pick and Place Operations - Saputro, Adi Kurniawan; Rahmawati, Diana; Febriana, Iftitah; Ibadillah, Achmad Fiqhi; Ulum, Miftachul; Haryanto, Haryanto (Jambura Journal of Electrical and Electronics Engineering, 2025)
In the modern era, robotic technology becomes essential for increasing efficiency and productivity in various sectors, including industry. One common robot application is the robot arm for pick-and-place tasks. This research aims to develop a robot arm with four degrees of freedom (DoF). The robot arm is designed to place glasses into packaging boxes. This research uses the principle of inverse kinematics and robot arm control software developed using Python programming language. The robot arm will be controlled using proximity sensors to read object distances or locations. The packaging process will be optimized through accurate and efficient movement planning from the conveyor to the cardboard position. Trial scenarios will be conducted to test the robot arm's ability to place glasses into packaging boxes with high accuracy. The trials were conducted 30 times within a 10-minute duration, achieving an accuracy of 99.9% for the x-y coordinates when the robotic arm picked up glasses. The accuracy of the robotic arm in placing glasses into the packaging box was 100% for the x-coordinate and 99.9% for the y-coordinate. The discrepancies in the robot's angular accuracy are attributed to inaccuracies in angle measurement, caused by uncertainties in determining the primary reference point of the stepper motor, which serves as the basis for its movement.Dalam era modernisasi, teknologi robotika menjadi esensial untuk meningkatkan efisiensi dan produktivitas di berbagai sektor, termasuk industri. Salah satu aplikasi yang umum digunakan adalah robot arm dalam tugas pick and place. Penelitian ini bertujuan untuk mengembangkan robot arm dengan empat derajat kebebasan (DoF). Robot arm ini dirancang untuk menempatkan gelas ke dalam kotak pengemas. Penelitian ini menggunakan prinsip inverse kinematics dan software pengendali robot arm yang dikembangkan menggunakan bahasa pemrograman Python. Robot arm akan dikendalikan dengan sensor proximity untuk membaca jarak atau letak objek. Proses pengemasan akan dioptimalkan melalui perencanaan gerakan pengambilan gelas dari konfeyor ke posisi kardus secaara akurat dan efisien. Skenario uji coba akan dilakukan dengan menguji kemampuan robot arm dalam menempatkan gelas ke dalam kotak pengemas dengan akurasi tinggi. Hasil uji coba dilakukan sebanyak 30 kali dalam waktu 10 menit menggunakan robot arm dalam mengambil gelas untuk koordinat x-y sebesar 99,9%. Tingkat akurasi robot arm dalam meletakkan gelas ke dalam kotak pengemas untuk koordinat x sebesar 100% sedangkan untuk koordinat y sebesar 99,9%. Perbedaan dalam keakuratan sudut robot terjadi karena ketidaktepatan dalam pengukuran sudut pada robot. Ketidaktepatan ini disebabkan oleh ketidakpastian dalam menentukan titik referensi utama dari motor stepper, yang berfungsi sebagai acuan untuk pergerakannya.